Regulatory peptide receptors in human hepatocellular carcinomas. Issue 5 (1st November 1999) - Reubi, J C; Zimmermann, A; Jonas, S; Waser, B; Neuhaus, P; Läderach, U; Wiedenmann, B
Abstract : BACKGROUND: Overexpression of regulatory peptide receptors in selected human tumours is of diagnostic and therapeutic relevance. AIMS: To evaluate the expression of somatostatin, vasoactive intestinal peptide (VIP), substance P, cholecystokinin (CCK) A and B, and neurotensin receptors in hepatocellular carcinoma (HCC). METHODS: In vitro receptor autoradiography for the various peptide receptors using selective iodinated radioligands on tissue sections in 59 cases of HCC. RESULTS: 41% of HCC expressed somatostatin receptors; 47% expressed VIP receptors. VIP receptors were always identified in non-neoplastic liver tissue. Substance P receptors were only identified in 5% of HCC but in the majority of their peritumorous and intratumorous vessels. CCK-A and -B and neurotensin receptors were not detected in HCC. The somatostatin receptors showed high affinity for somatostatin and octreotide. The VIP receptors had high affinity for VIP, pituitary adenylate cyclase activating peptide (PACAP) 27, and a VIP1 selective analogue, suggesting the presence of VIP1/PACAP II type receptors. PACAP I receptors were identified in two cases. Substance P receptors were all of the NK1 subtype. The density of somatostatin receptors in HCC was low compared with the density found in liver metastases of neuroendocrine tumours. The VIP receptor density was always lower in HCC than in adjacent liver tissue. CONCLUSIONS: Somatostatin, VIP, and substance P may have a receptor mediated role in HCC. Substance P receptors may be involved in regulation of tumour associated blood flow; somatostatin receptors and VIP receptors may mediate tumour growth. Diagnostic and therapeutic evaluation of somatostatin and VIP analogues may be of interest in receptor positive HCC.